Persepsi Mahasiswa Kedokteran Ukrida Angkatan 2020 terhadap Proses Pembelajaran Daring - Arsana, Gabriel Ferdinan; Hartono, Budiman; Josephine, Jodie (Universitas Kristen Krida Wacana, 2024)
Online learning is leaning that utilizes online media or the internet in learning. The learning process that is carried out online makes students’ psychological and mental activities trained in the environment, which results in a pile of changes in knowledge and understanding, skills and attitude values. Perception is a point of view or understanding of material or information received during learning activities. This study has four operational definitions, namely online learning, problem-based learning, skills lab, and integration. From the results of this study, it was concluded that students have perceptions of online learning satisfaction because students can study anywhere during the pandemic and can understand the material presented by lecturers. Based on the level of achievement of student respondents, they can take part in online learning without affecting the learning process or behavior.